2019
DOI: 10.32789/publichealth.2019.1004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Front-of-Package Traffic Light (FoPTL) Nutrition Label Design on the Acceptability and Understanding of Nutrition Labels for Hypertension Patients

Abstract: The practice of reading nutrition labels and understanding the information still remains low in Indonesia, especially among hypertensive patients. Yet, Front-of-Package Traffic Light (FoP-TL) labels can be well received by the community compared to information labels that display nutritional values. Hypertension sufferers need to understand such FoP-TL labels in order to be aware of their sodium consumption and not exceed recommended limits. The purpose of this study was to assess the effect of nutrition label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This showed that traffic light colors are favorable signals for acceptability and understanding of nutrition. 16 We supposed that a VNI using traffic light colors can provoke the physician to modify their NT prescription. The results were promising.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that traffic light colors are favorable signals for acceptability and understanding of nutrition. 16 We supposed that a VNI using traffic light colors can provoke the physician to modify their NT prescription. The results were promising.…”
Section: Discussionmentioning
confidence: 99%